An intensive review on the role of graphene oxide in cement-based materials. (30th April 2020) - Zhao, Li; Guo, Xinli; Song, Luguang; Song, Yang; Dai, Guozhong; Liu, Jiaping
Highlights: The effects of GO on cement composites have been extensively reviewed and analyzed. The dispersion of GO in cement composites is the most important parameter. Some concerns regarding the dispersion of GO with the aid of PCE are summarized. The hybrid of GO with other materials can bring further reinforcement. Abstract: Graphene oxide (GO) has been given a great interest for the use as nano-reinforcement in cement composites due to its exceptional mechanical properties and active functional groups. However, the role of GO in cement-based materials has not been elucidated in the literature because of some inconsistent results. This paper aims at providing an intensive review on the reinforcing effects and mechanisms of GO on cement composites by consulting a lot of correlative literature, mainly focusing on the following aspects: (I) the dispersion issue of GO in the alkaline cement paste; (II) the effects of GO on the macro-performance (workability, mechanical strength, and durability) of cement composites; (III) the reinforcing mechanisms of GO including hydration kinetics, C-S-H structure, pore structure, and interfacial bonding with cement matrix. At last, the novel studies on the hybrid of GO with other materials towards further reinforcement and multifunctionality in cement composites are shared. This review may present a clear understanding of the reinforcing role of GO in cement-based materials and arouse new ideas to promote its practical application in construction materials.